Social isolation and intrinsic capacity among left-behind older adults in rural China: The chain mediating effect of perceived stress and health-promoting behavior - Su, Hong; Xu, Lijuan; Yu, Hong; Zhou, Yuqiu; Li, Yang (Frontiers in Public Health, 2023)
Background:Strengthening and maintaining the intrinsic capacity (IC) of the elderly is the key to preventing and delaying disability as well as promoting healthy aging. Objective:This study explores the relationship between social isolation, perceived stress, health promotion behavior, and IC of the left-behind elderly in rural areas, and analyzes the chain mediating effect of perceived stress and health promotion behavior among social isolation and IC. Methods: Multi-stage sampling method was used for recruiting the participants from rural areas in Heilongjiang Province, China, from March 2021 to May 2022. Data were collected with the simplified version of the Lubben Social Network Scale, the Chinese Perceived Stress Scale, the Health-Promoting Lifestyle Profile-Chinese and the Integrated Care for Older People (ICOPE) screening tool. We used the PROCESS macro for SPSS to determine the mediating effect of perceived stress and health-promoting behavior between social isolation and IC Result: Social isolation was positively correlated with health-promoting behavior(r = 0.78, p<0.01) and IC (r = 0.67, p<0.01), whereas it was negatively correlated with perceived stress (r =-0.63, p<0.01). Perceived stress was negatively correlated with health-promoting behavior (r = –0.62, p<0.01) and IC (r = –0.43, p<0.01). The health-promoting behavior and IC were positively correlated (r = 0.56, p<0.01). Bootstrapping values indicated that the chain mediating effect of perceived stress and health-promoting behavior was statistically significant. Conclusion:Consequently, to improve the IC of the left-behind elderly, we should focus more on reducing the degree of social isolation of the left-behind elderly and improving their perceived stress as well as health-promoting behavior.